Well-Being Washing: Illusory Employee Care in an Organisation - Mikołajczyk, Katarzyna (Well-being washing – iluzoryczna troska o pracowników w organizacji, 2025)
Aim: The article explores the issue of well-being washing, identifying its indicators and impact on employees and organizations, while outlining the key components of effective organizational well-being strategies. Methodology: The study presents findings from a Focus Group Interview (FGI) conducted with eight employees from large Polish organizations across various industries. The qualitative data were analysed to evaluate well-being practices in their companies and determine whether they exhibited characteristics of well-being washing. Results: The research reveals that well-being washing practices are prevalent in most examined organizations. While the respondents identified various well-being initiatives, these were often superficial, lacking alignment with business strategies and a holistic approach. The practices were typically ad-hoc and did not address employees’ genuine needs. Implications and recommendations: The study highlights the negative implications of well-being washing for employees and organizations. It underlines the importance of developing authentic, well--aligned well-being strategies. Future research should explore effective interventions to counteract well-being washing and promote meaningful well-being initiatives. Originality/value: This research addresses the underexplored concept of well-being washing, revealing its prevalence and adverse effects. By critically analysing the existing practices, it contributes to understanding the gap between declared and actual well-being efforts in organizations, emphasising the importance of authenticity in employee care initiatives.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 2, s. 90-100